57.1k views
2 votes
-6x - 29 = 5x - 7 (This is Finding the Common Denominator)

User Bochgoch
by
6.0k points

2 Answers

3 votes
-6*x-29-(5*x-7)=0

-11x - 22 = -11 • (x + 2)

Solve : -11 = 0

Solve : x+2 = 0

x = -2
User Amir Molaei
by
5.9k points
4 votes
if you add 6x to 5x you get 11x and then if you add 7 to -29 you get -22... so your equation will look like this-
-22=11x
which both can be divided by 11 which makes the common denominator 11. and if you wanted to solve it the answer would be- x=-2
User Bdeem
by
5.6k points